Diverse placement experiences and professional identity development. Perceptions of trainee teachers based within the post-compulsory sector - Amanda Turner; Anastasija Jumatova (Educational Futures)
This article explores the experiences of trainee teachers on placement which forms their professional identity. This article focusses on trainee teachers based in the Further Education (FE) and Skills sector, in England.